1995
DOI: 10.1007/bf00197064
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive radiological features of small hand joints in rheumatoid arthritis and seronegative spondyloarthritis demonstrated by contrast-enhanced (Gd-DTPA) magnetic resonance imaging

Abstract: A series of patients with clinically early inflammatory joint disease due to rheumatoid arthritis, psoriatic arthritis and Reiter's syndrome were examined by plain film radiography and magnetic resonance imaging (MRI). The spin echo T1-weighted precontrast, T2-weighted, and, especially, T1-weighted postcontrast images demonstrated distinct differences in the distribution of inflammatory changes, both within and adjacent to involved small hand joints. Two major subtypes of inflammatory arthritis were shown, thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0
9

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(110 citation statements)
references
References 12 publications
3
96
0
9
Order By: Relevance
“…OA was diagnosed when the collateral ligaments were abnormal, with collateral ligament-related abnormalities, such as bone edema, bone erosions, osteophytes, and cartilage loss, as previously described (8). The diagnosis of PsA was based on the presence of enthesitis, diffuse bone edema, and extracapsular edema, as previously described in this condition (9,10), as well as the absence of features of OA.…”
Section: Methodsmentioning
confidence: 91%
“…OA was diagnosed when the collateral ligaments were abnormal, with collateral ligament-related abnormalities, such as bone edema, bone erosions, osteophytes, and cartilage loss, as previously described (8). The diagnosis of PsA was based on the presence of enthesitis, diffuse bone edema, and extracapsular edema, as previously described in this condition (9,10), as well as the absence of features of OA.…”
Section: Methodsmentioning
confidence: 91%
“…Regarding hand joints, Offidani, et al 15 reported signs of occult synovitis by MRI that were found in 68% of patients including joint or tendon sheath effusions, bone erosions, and BME. In established cases of PsA, Jevtic and coworkers 16 using MRI described inflamed tissue in the hand joints extending far beyond the joint capsule, thickened collateral ligaments, and surrounding periarticular soft tissue, a pattern that is quite different from that observed in patients with RA. In another report, Tan, et al 17 showed, using MRI, prominent inflammatory changes in ligament, tendon, enthesis, and adjacent bone in the distal interphalangeal (DIP) joints of patients with PsA, and similar findings were observed in DIP joints among patients with osteoarthritis (OA) but to a lesser extent.…”
Section: Discussionmentioning
confidence: 98%
“…A General Electric echo speed 1.5-Tesla MR unit equipped with a dedicated cylindrical knee coil was used. Sagittal, coronal, and axial T1-weighted spin-echo MR images were obtained with the following MRI sequences: coronal T2-weighted TR: repetition time (TR)/echo time (TE) 2600−24/68, matrix size 256 × 160, section thickness 4 mm, spacing 0.5 mm, field of view (FOV) 16 Interpretation of MRI findings. MR images were evaluated for the following radiological signs before and after intravenous contrast injection: BME, perientheseal BME, bone erosions, cartilaginous erosions, synovial enhancement and degree of synovial thickness, Baker's cyst, periarticular soft-tissue edema, and knee effusion.…”
Section: Severitymentioning
confidence: 99%
“…The inaugural workshop on enthesitis was a gathering of interested parties, convened in Berlin following recognition of the importance of enthesitis in synovial joint disease in SpA (1); proceedings of that workshop have been reported elsewhere (2). The Second International Enthesitis Workshop, which was held in Leeds March [15][16]2002, emphasized recent advances in the study of enthesitis, in particular the relationship of biomechanical factors and osteitis to enthesitis. Additionally, the emerging evidence for a unifying anatomic basis for SpA based on the concept of enthesitis was reviewed.…”
mentioning
confidence: 99%